Tendencje w pomiarze regionalnej innowacyjności - podejście amerykańskie - Markowska, Małgorzata (Tendencies in the Measurement of Regional Innovativeness - American Approach, 2006)
The study presents research results and experiences of American research workers in measuring American innovativeness. The presented approach based on matrix aims at pointing to innovation priorities and observations of annual results in key areas. The articles describes main objectives and discusses their influence on innovativeness level as well as presents results of empirical studies performed in the period of two years in the state of Misissippi.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 222-232